2015
DOI: 10.1016/j.ntt.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal cocaine exposure on pubertal development

Abstract: The purpose of the current study was to examine the relationship between prenatal cocaine exposure (PCE) and pubertal development. Children (n=192; 41% with PCE) completed the Pubertal Development Scale (Petersen, et al. 1988) and provided salivary dehydroepiandrosterone (DHEA) samples at 6 month intervals from 11 to 13 years. PCE was examined as a predictor of pubertal status, pubertal tempo, and DHEA levels in mixed models analyses controlling for age, sex, environmental risk, neonatal medical problems, othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 106 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…For example, recent studies have shown in teens with PCE problems of social interaction (Greenwald, Chiodo et al 2011) and adolescent substance use (Delaney-Black, Chiodo et al 2011, Chaplin, Visconti et al 2014). Although these problems may also be influenced by prenatal exposure of other drugs and environmental factors (Lambert and Bauer 2012), may mainly occur in an emotional context (Mayes 2002), or may simply reflect delayed maturation (Bennett, Birnkrant et al 2015), these findings still suggest the importance of a deeper understanding the impact of PCE on the developing brain, particularly on the interplay of cognitive and limbic systems. In typically developing adolescents, the ability to regulate emotion and attention increases substantially (Crone and Dahl 2012) with children demonstrating decreasing emotional arousal (Guyer, Monk et al 2008) and increasing executive functioning (Giedd 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have shown in teens with PCE problems of social interaction (Greenwald, Chiodo et al 2011) and adolescent substance use (Delaney-Black, Chiodo et al 2011, Chaplin, Visconti et al 2014). Although these problems may also be influenced by prenatal exposure of other drugs and environmental factors (Lambert and Bauer 2012), may mainly occur in an emotional context (Mayes 2002), or may simply reflect delayed maturation (Bennett, Birnkrant et al 2015), these findings still suggest the importance of a deeper understanding the impact of PCE on the developing brain, particularly on the interplay of cognitive and limbic systems. In typically developing adolescents, the ability to regulate emotion and attention increases substantially (Crone and Dahl 2012) with children demonstrating decreasing emotional arousal (Guyer, Monk et al 2008) and increasing executive functioning (Giedd 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Establishing the causal effect of PCE on early sexual behavior is complicated due to multiple biological and environmental confounders, including high levels of prenatal exposure to other substances such as alcohol (Larkby et al, 2011), tobacco (Maughan et al, 2004), and marijuana (Goldschmidt et al, 2000), elevated lead (≥ 10 μg/dL)levels (Lane et al, 2008; Min et al, 2009; Singer et al, 2008), delayed pubertal development (Bennett et al, 2015), poor quality of the home environment (Lewis et al, 2011; Singer et al, 2008), caregiver postpartum substance use and psychological distress (Minnes et al, 2010) and adoptive/foster care placement (Singer et al, 2004). Further, family conflict (Fosco et al, 2012), violence exposure (Frank et al, 2011), poor attachment to caregiver (Warner et al, 2011), and inadequate parental monitoring (Min et al, 2014a, 2014b), all reflecting the interpersonal developmental contexts in which adolescents transact (Cicchetti and Rogosch, 2002), may heighten the drug exposed adolescent’s vulnerability.…”
Section: Introductionmentioning
confidence: 99%